2022
DOI: 10.1002/sys.21649
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual modeling to support system‐level decision‐making: An industrial case study from the Norwegian energy domain

Abstract: This article explores conceptual modeling to support system‐level decision‐making during concept evaluation. The system‐level decisions made in the concept phases decide most of the systems' value and cost. The context for our research is the Norwegian energy domain. Through an industrial case study in a global subsea system supplier company, we have explored conceptual modeling to support system‐level decision‐making in the conceptual phase. From the insights and learnings gained in the industry case, the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Examples of industrial Ph.D. studies are the theses of Kjørstad [6] and Engen [7]. In their research, they worked with Industry master's students carrying out their master's project.…”
Section: History Of the Industry Master Programmentioning
confidence: 99%
“…Examples of industrial Ph.D. studies are the theses of Kjørstad [6] and Engen [7]. In their research, they worked with Industry master's students carrying out their master's project.…”
Section: History Of the Industry Master Programmentioning
confidence: 99%
“…To reconcile the different views and mental models of different stakeholders and the architect, Muller (2014) uses conceptual models. Engen et al (2022) found conceptual models helpful in exploring the impact of early-phase project decisions. As we will show in later chapters, we also use formal and informal models for explaining the end-model.…”
Section: Systems Architectingmentioning
confidence: 99%